Takagi Sugeno Fuzzy Controller for ITER Poloidal Field ac/dc Converter Using Active Power Filter. (19th May 2019) - Hassan, Mahmood Ul; Fu, Peng; Song, Zhiquan; Muhammad, Humayun; Hua, Li; Zhang, Xiuqing
Abstract: This paper presents a novel technique using a shunt active power filter (SAPF) control strategy to reduce the harmonics generated by the power converter. A three-phase SAPF using the Takagi Sugeno (TS) fuzzy technique is used to reduce current distortion. The proposed TS fuzzy controller is a suitable candidate using SAPF techniques. In order to realize an acceptable distortion limit, TS fuzzy control uses SAPF to realize the performance of the system. The simulation results validate the proposed fuzzy control strategy by a Matlab/Simulink model.